Taking ideas and words seriously: explaining the institutionalization of the Lancang-Mekong cooperation - Gong, Xue (2024)
This article explores the role of China’s ideational and discursive power in shaping the interest perceptions of target states and in determining the formation of a new institution. Using the Lancang-Mekong Cooperation (LMC) as a case study, this article illustrates how China framed the idea of institutionalization, and how such idea was proposed, articulated, deliberated, and accepted in the interactions with partner countries. Relying on a collection and coding of over 700 Chinese official texts on the LMC and extensive interviews, we analyze how the Chinese authorities have used ideas and discourses to garner support from states in the Mekong region for the establishment of the institution. This article demonstrates that China’s ideational and discursive power helps generate three outcomes: preference denying, preference cultivating, and preference empowering. Such Chinese power has helped align Mekong countries’ interest perceptions with China’s expectations in three ways: transforming water security into developmental issues, accepting Chinese proposals through tactical persuasion, and constraining alternative policies.